TECHNOLOGICAL EVALUATION OF AROMATIC HOP VARIETIES OF UKRAINIAN SELECTION - Бобер, Оксана; Бобер, Анатолий; Проценко, Лидия (SWorldJournal, 2020)
The article presents the results of technological evaluation of aromatic hop varieties of different maturity groups of Ukrainian selection. It is established that among the zoned varieties there are both high-quality varieties and those with low technolog